NIR-driven graphitic-phase carbon nitride nanosheets for efficient bioimaging and photodynamic therapy. Issue 48 (28th November 2016) - Feng, Lili; He, Fei; Yang, Guixin; Gai, Shili; Dai, Yunlu; Li, Chunxia; Yang, Piaoping
Abstract : Photodynamic therapy (PDT) is a noninvasive and promising anticancer therapy modality that utilizes the photochemical reactions of photosensitizers, upon irradiation at a specific wavelength, to yield reactive oxygen species (ROS) to impair malignant cancer cells. Abstract : Photodynamic therapy (PDT) is a noninvasive and promising anticancer therapy modality that utilizes the photochemical reactions of photosensitizers, upon irradiation at a specific wavelength, to yield reactive oxygen species (ROS) to impair malignant cancer cells. As a potential and new two-dimensional layered photosensitizer, graphitic-phase carbon nitride (g-C3 N4 ) exhibits a high blue photoluminescence quantum yield and good biocompatibility, but is challenged by limited narrow absorption in the near-infrared (NIR) region. Herein, in order to broaden its light utilization, unique and original NIR light excited nanocomposites (g-C3 N4 /UCNP NCs) for PDT based on g-C3 N4 nanosheets combined with up-conversion nanoparticles (UCNPs) have been designed. UCNPs can efficiently convert NIR light to ultraviolet and visible light emissions that match well with the absorption of g-C3 N4 nanosheets. The nanocomposites swallowed up by cancer cells are able to yield ROS and suppress tumor cell growth and then induce apoptosis upon NIR laser excitation. This demonstrates the potential of g-C3 N4 /UCNP NCs as a low-toxic and biocompatible photosensitizer for PDT and for down/up-conversion luminescence imaging.